2022
DOI: 10.3389/fpls.2022.942004
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome resequencing identified QTLs, candidate genes and Kompetitive Allele-Specific PCR markers associated with the large fruit of Atlantic Giant (Cucurbita maxima)

Abstract: Atlantic Giant (AG) pumpkin (Cucurbita maxima) produces the world’s largest fruit. Elucidating the molecular mechanism of AG fruit formation is of scientific and practical importance. In this research, genome-wide resequencing of an F2 population produced by a cross between AG and its small-fruit ancestor Hubbard was used to identify quantitative trait loci (QTLs) and candidate genes. Transgressive segregation of fruit size-related traits was observed in the F2 population, suggesting that fruit size was a quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…Spraying NAA can improve the fruit size and single-fruit quality of plums, blueberries, guavas, ber, and other fruit crops, promoting higher yield per plant [ 13 , 14 , 15 , 16 ]. EBR can improve the yield of wheat, rice, and cucumber, among other crops [ 9 , 12 , 18 ]. However, there were few reports on the use of growth regulators to increase pumpkin fruit weight; especially the application of NAA and EBR on pumpkin has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spraying NAA can improve the fruit size and single-fruit quality of plums, blueberries, guavas, ber, and other fruit crops, promoting higher yield per plant [ 13 , 14 , 15 , 16 ]. EBR can improve the yield of wheat, rice, and cucumber, among other crops [ 9 , 12 , 18 ]. However, there were few reports on the use of growth regulators to increase pumpkin fruit weight; especially the application of NAA and EBR on pumpkin has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were few reports on the use of growth regulators to increase pumpkin fruit weight; especially the application of NAA and EBR on pumpkin has not been reported yet. Previously, we found that the SNPs alterations in the IAA, BR, and ER pathways may improve fruit enlargement and proposed that auxin and brassinolide may play important roles in giant pumpkin fruit growth [ 18 ]. Therefore, this study sought to reveal the effects of applying two growth regulators (NAA and EBR) at different concentrations and at different growth stages on fruit expansion to identify control measures to further improve giant pumpkin-fruit size.…”
Section: Introductionmentioning
confidence: 99%
“…The largest allelic effect in this GWAS for fruit size was of LRR receptor-like kinase (RLK), consistently shown across the years. This gene was also major marker for fruit size increase in a high-resolution genetic mapping of a biparental cross involving Atlanta giant and hubbard ( Pan et al, 2022 ). In a yeast two-hybrid assay in strawberry, RLK showed an interaction with a putative ABA receptor, which in turn induced ABA and ethylene ( Hou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this study is to elucidate the genome-wide molecular diversity and evolution in a representative collection involving major groups of C. maxima , and determine genetic factors underlying the growth and development of the giant pumpkins (Guinness World Records, 2021) ( Pan et al, 2022 ). It aimed to reveal the genetic components of the mammoth horticulture group with reference to the other horticulture groups and explore the possible genetic factors underlying the giant fruit growth.…”
Section: Introductionmentioning
confidence: 99%
“…Auxin synthesis is mainly determined by two main enzymes, tryptophan aminotransferase of Arabidopsis/tryptophan aminotransferase related (TAA1/TAR) and flavin monooxygenase (YUCCA) in plants [ 11 ]. Then, auxin is transported by auxin resistant 1/like auxin resistant 1 (AUX1/LAX1) and PIN-formed 1 (PIN1) from extracellular to intracellular and in the reverse direction after auxin synthesis, respectively [ 12 ]. In addition to its synthesis and transport, auxin is degraded by gretchen hagen 3 (GH3) family protein [ 8 ].…”
Section: Introductionmentioning
confidence: 99%